Nature obscura : a city's hidden natural world - Brenner, Kelly (Mountaineers Books, 2020)
"With wonder and a sense of humor, Kelly Brenner aims to help us rediscover our connection to the natural world that is just outside our front door--we just need to know where to look. Through explorations of a rich, varied urban landscape, Brenner reveals the complex micro-habitats and surprising nature that exists in the middle of a city. In her hometown of Seattle, which has plowed down hills, cut through the land to connect fresh- and saltwater, and paved over much of the rest, she exposes a diverse range of often unnoticed creatures. 'Nature Obscura' explores the species that inhabit the urban environment across the four seasons"--